Advances in physical organic chemistry. - Tidwell, Thomas T., 1939-; Richard, J. P. (John P.) (Academic Press, 2001)
Advances in Physical Organic Chemistry provides the chemical community with authoritative and critical assessments of the many aspects of physical organic chemistry. The field is a fast developing one, with results and methodologies finding application from biology to solid state physics. The previous volumes in this serial constitute a lasting record of this field and will continue to do so as they are widely used and cited. Readers will also benefit from the comprehensive subject and citation index.